Progress in adsorption capacity of nanomaterials for carbon dioxide capture: A comparative study. (15th December 2021) - Firdaus, Rabita Mohd; Desforges, Alexandre; Rahman Mohamed, Abdul; Vigolo, Brigitte
Abstract: With the gradual rise in atmospheric carbon dioxide brought about by human activities and industry effluents, research has now been geared toward carbon capture and storage. To achieve high carbon dioxide adsorption capacity, development of nanomaterials with optimized properties has been attracting growing interest for more than ten years already. Such multi-parameter investigations require a complex and rigorous analysis in order to compare the different developed adsorbents and improve their performances. In this review, we propose a state-of-the-art approach related to the four most studied nanostructured adsorbents for carbon dioxide capture: graphene, carbon nanotubes, zeolite, and metal organic frameworks. The capture processes and the nanomaterials of interest were described as well as the modifications applied to improve the efficiency of carbon dioxide capture. The present unprecedented analysis allows to correlate the nanomaterial properties, especially surface area and pore volume, to the CO2 adsorption capacity. The results reveal that contrary the popular belief, the CO2 capture improvement is not solely liable on the high surface area and the high pore volume of the nanosorbents. This outcome may be useful in the course of improvement of nanostructured materials for CO2 capture for future technologies. Graphical abstract: Image 1